2021
DOI: 10.1186/s13023-021-01692-w
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular mechanics and dynamic simulations of well-known Kabuki syndrome-associated KDM6A variants reveal putative mechanisms of dysfunction

Abstract: Background Kabuki syndrome is a genetic disorder that affects several body systems and presents with variations in symptoms and severity. The syndrome is named for a common phenotype of faces resembling stage makeup used in a Japanese traditional theatrical art named kabuki. The most frequent cause of this syndrome is mutations in the H3K4 family of histone methyltransferases while a smaller percentage results from genetic alterations affecting the histone demethylase, KDM6A. Because of the rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…We focus more on the local chemical environment and geometry of the key reactive groups. The influence of the p K a shift has been already noticed and presented in our publication [13] . However, the influence of local geometry has not been explored.…”
Section: Methodssupporting
confidence: 57%
See 2 more Smart Citations
“…We focus more on the local chemical environment and geometry of the key reactive groups. The influence of the p K a shift has been already noticed and presented in our publication [13] . However, the influence of local geometry has not been explored.…”
Section: Methodssupporting
confidence: 57%
“…Next, additional information comes from the RMSFs of each amino acid, which highlights the flexible regions of the systems. Atomic RMSFs from the average structure in the trajectory were calculated for each residue and plotted as shown in our publication [13] . Finally, we computed the time-dependent binding free energy for all cases as well as radius of gyration (Rg) and dynamic solvent accessible-accessible surface area (SASA) using the protocols implemented in the Discovery Studio.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both KDM6A and KMT2D are components of the activation signal cofactor complex whose function is to remove inhibitory epigenetic markers and deposit activated methylation markers on the chromatin, and then recruit RNA polymerase II complex to activate chromatin[ 19 ]. A previous study demonstrated that the KDM6A KS variants might impair functions of the histone demethylase through various mechanisms, including alteration of the protein integrity, local environment, molecular interactions and protein dynamics[ 20 ]. KDM6A protein plays a critical role in cell differentiation, development, and cancer, and is also important in differentiation of embryonic stem cells and development of various tissues, and alteration of KDM6A protein functions and expression results in developmental defects, growth retardation, multiple congenital organ malformations, and hematological and immunological anomalies[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the publication of the original article [ 1 ], the authors became aware of the work by Petrizzelli et al, 2020 [ 2 ]. The two studies truly represent independent works, for which contents are different.…”
Section: Correction To: Orphanet J Rare Dis (2021) 16:66 101186/s13023-021-01692-wmentioning
confidence: 99%